Teaching in the developing nations : a guide for educators - Tibbetts, John; Akeson, Merle ;Silverman, Marvin (Belmont, California : Wadsworth Publishing Company, 1968)
This guide is an introductory source, focused on the main operations of overseas teaching: cultural conflicts, learning, teaching strategies, materials, evaluation, and sources of additional professional information. It also looks candidly at school conditions prevalent among the developing countries.
1. School and community -- 2. The Learning Process -- 3. Teaching strategies -- 4. Methods and materials -- 5. Evaluation.
Includes bibliographical references and index.
Keywords: EDUCATION -- DEVELOPING COUNTRIES